Management of central nervous system Rosai-Dorfman disease: A single center treatment experience. (May 2022) - Zhu, Qiang; Liang, Yuchao; Fan, Ziwen; Liu, Yukun; Zhou, Chunyao; Zhang, Hong; Li, Tianshi; Zhou, Yanpeng; Yang, Jianing; Wang, Lei
Highlights: 1. RDD involved in CNS is a rare heterogeneous disease with various clinical manifestations, which pose a major diagnostic challenge. 2. There is no unified treatment consensus, and the treatment mainly relies on the experience of clinicians. 3. This study has reported a series of patients diagnosed with RDD-CNS. We summarized the imaging characteristics and treatment experience of the single institute. We think this study would improve the awareness that may lead to the deeper understand of RDD-CNS, and develop optimum treatment strategy. Abstract: Rosai-Dorfman disease (RDD) is an idiopathic histiocytic proliferation disease with various clinical manifestations. A retrospective study of patients with pathological diagnosed RDD primarily involved in the central nervous system was conducted from January 2011 to December 2020 at a tertiary center. The clinical profile, imaging, and treatment data were collected. There were 16 male and 5 female patients with RDD-CNS. The patients were aged from 6 to 68 years with a median of 37 years. Of these 21 patients, 15 presented with intracranial RDD and 6 with spinal RDD. The main symptoms of RDD-CNS included headache, epilepsy, and neurological deficits. 76.19% (16/21) of the patients showed dura-based, homogeneous enhancement lesion on magnetic resonance imaging (MRI). Twenty patients received surgery as first treatment, and one patient received biopsy after steroid therapy. Total lesion resection was achieved in 42.9% (9/21) of the patients, subtotal resection in 47.6% (10/21), and biopsy in 0.9% (2/21). The symptoms were alleviated or stayed stable. Some RDDs (80%, 4/5) in the skull base had some complications. The patients were followed up for 11–108 months with a median duration of 47 months. Lesion progression or recurrence was found in two patients. The various clinical manifestations, as well as the dura-based and homogenous enhancement imaging profiles of RDD-CNS patients pose a great diagnostic challenge for clinicians. Surgery is effective for RDD-CNS requiring treatment. Medical therapy and radiotherapy would be feasible as noninvasive treatments, varying degrees of efficacy. The overall prognosis of RDD-CNS is acceptable. Periodic long-term follow-up is necessary.